(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2014)
That the structural changes in the environment, business and finance and the spread of business and the diversity of transactions between economic organizations and breadth of a commercial scale in the world have left their clear on the need to keep up with the accounting for these variables as one of the social sciences affect and are affected by the surrounding environment because of the various economic and social factors, technical, legal and others. As a result of these variables emerged a new field of accounting called Forensic Accounting, which involves the use of expertise of multiple pour in the end to the accounting profession, where the Forensic Accounting cover a large area of ​​disciplines including strengthening judicial decisions, acts of investigations, detection of fraud, corruption and settlement of conflict resolution , and over time take this area to evolve He played an important role in the activation of the concept of corporate governance, which increased interest in the impact of recurring financial crises that led to the bankruptcy of many companies, due to the spread of corruption accounting reflux to the non-application of accounting principles and the lack of disclosure and transparency and do not show the data and factual information that reflect the financial situation of the units economic, resulting in a loss of confidence in the accounting information contained in the financial statements, and thus the loss of accounting information for the most important elements of excellence (quality). So it became a corporate governance effective tool to ensure the objectivity Altaqariralamalah, and this through a commitment to apply the principle of disclosure and transparency. All of this confirms the existence of a close link between the application of the principles of governance and the quality of accounting information as are considered the two sides of the same coin affects and is affected by the other.